Light Exposure, Physical Activity, and Indigeneity Modulate Seasonal Variation in NR1D1 (REV-ERBα) Expression - Denis Gubin; Sergey Kolomeichuk; Konstantin Danilenko; Oliver Stefani; Alexander Markov; Ivan Petrov; Kirill Voronin; Marina Mezhakova; Mikhail Borisenkov; Aislu Shigabaeva; Julia Boldyreva; Julianna Petrova; et al. (Biology, 2025)
Nuclear receptor subfamily 1 group D member 1 (NR1D1 or REV-ERBα) is a crucial element of the circadian clock’s transcriptional and translational feedback loop. Understanding its expression in humans is critical for elucidating its role in circadian rhythms and metabolic processes, and in finding potential links to various pathologies. In a longitudinal survey, we examined REV-ERBα expression at 08:00 using a real-time polymerase chain reaction (qRT-PCR) in blood mononuclear cells from Arctic native and non-native residents during equinoxes and solstices. REV-ERBα expression exhibited a pronounced seasonality, peaking at the summer solstice, and reaching a nadir at the winter solstice in both natives and non-natives, with a relatively higher summer peak in natives. After adjusting for age, sex, and body mass index, the amount and timing of light exposure, the amount of physical activity, and indigeneity emerged as significant predictors of REV-ERBα expression.